Three-dimensional microarchitecture of the human placental villous tree in health and disease - Barapatre, Nirav; Frank, Hans-Georg (Frontiers in Cell and Developmental Biology, 2025)
BackgroundPlacental dysfunction plays a central role in pregnancy complications such as fetal growth restriction (FGR), preeclampsia (PE), and gestational diabetes mellitus (GDM). Recent advances in 3D microscopy and stereological analysis have revealed microanatomical changes not detectable by conventional histology.ObjectiveTo summarise key morphological and cellular alterations in the human placenta across FGR, PE, and GDM, with a focus on architecture of the villous tree, proliferative trophoblast dynamics, and sex-specific adaptations.MethodsA synthesis of quantitative 3D histological studies was undertaken, focusing on villous compartment volumes, trophoblast proliferation markers (PCNA), nuclear distribution patterns, and branching indices in placentas from affected and control pregnancies.ResultsFGR placentas exhibit central loss of contractile villi (C-villi), increased syncytial nuclear density, and abolished sexual dimorphism. In PE, peripheral villous volume (NC-villi) is reduced, with marked increased proliferation of trophoblast in female placentas and disrupted nuclear spacing. GDM placentas show a global reduction in villous branching and altered proliferative dynamics of villous trophoblast, particularly in females, already in the absence of placental macrosomia.ConclusionDespite distinct clinical profiles, FGR, PE, and GDM exhibit specific yet partially overlapping placental microstructural pathologies, characterised by trophoblast dysregulation and sex-specific adaptations. These findings underscore the significance of fetal sex and quantitative three-dimensional morphometry in advancing our understanding of placental disease mechanisms.